1995
DOI: 10.1093/oxfordjournals.humrep.a136174
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Effects of nitric oxide on human spermatozoa: evidence that nitric oxide decreases sperm motility and induces sperm toxicity

Abstract: Endogenous nitric oxide (NO) is an important functional mediator in several physiological systems, including the reproductive system. However, when generated in excessive amounts for long periods, mainly during immunological reactions, NO is cytotoxic and cytostatic for invading microbes, as well as for the cells generating it and the tissues present around it. Since infertility associated with urogenital tract infection in males and females is also accompanied by reduced sperm motility and viability, it is po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
132
0
8

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(147 citation statements)
references
References 19 publications
(40 reference statements)
7
132
0
8
Order By: Relevance
“…Accordingly, human sperm motility is inhibited by the NOS inhibitor N G -nitro-L-arginine methyl ester and by the NO scavenger methylene blue (Lewis et al 1996, Donnelly et al 1997. On the other hand, high NO concentrations (25-125 mM pure NO, 0.25-2.5 mM sodium nitroprusside, 12-600 mM S-nitroso-N-acetylpenicillamine, and 100-125 mM 3-morpholinosydnonimine) seem to exert opposite effects on the motility of human spermatozoa in vitro (Rosselli et al 1995, Weinberg et al 1995, Nobunaga et al 1996. Studies on sperm capacitation showed that NO (1-100 mM spermine NONOate (SPNO) or diethylamine-NONOate) increases cAMP levels, thus triggering protein kinase A activation and tyrosine phosphorylation (Herrero et al 2000) and is also involved in activation of protein ERKs (Thundathil et al 2003, O'Flaherty et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, human sperm motility is inhibited by the NOS inhibitor N G -nitro-L-arginine methyl ester and by the NO scavenger methylene blue (Lewis et al 1996, Donnelly et al 1997. On the other hand, high NO concentrations (25-125 mM pure NO, 0.25-2.5 mM sodium nitroprusside, 12-600 mM S-nitroso-N-acetylpenicillamine, and 100-125 mM 3-morpholinosydnonimine) seem to exert opposite effects on the motility of human spermatozoa in vitro (Rosselli et al 1995, Weinberg et al 1995, Nobunaga et al 1996. Studies on sperm capacitation showed that NO (1-100 mM spermine NONOate (SPNO) or diethylamine-NONOate) increases cAMP levels, thus triggering protein kinase A activation and tyrosine phosphorylation (Herrero et al 2000) and is also involved in activation of protein ERKs (Thundathil et al 2003, O'Flaherty et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, excessive NOS may induce the production of large amounts of NO metabolites in response to a variety of stressors, possibly reducing the survival rate and motility of sperm cells [18,20]. High levels of NO may also reduce testosterone secretion, as indicated by the suppression of testosterone secretion in male rats treated with the NO donor, isosorbide dinitrate (ISDN) [1].…”
mentioning
confidence: 99%
“…Estudos recentes mostraram que entre 40% e 88% dos homens com baixa fertilidade apresentam elevados níveis de EOR no plasma seminal (15 (24). Em situações de falha na regulação da ONS, ocorre uma excessiva produção de ON, que pode causar patologias aos espermatozóides, diminuindo a fertilidade (25).…”
Section: Oxidação Biológicaunclassified